Pollution assessment and mercury speciation of small-scale gold mine (SSGM) tailings, sediments, and ore from Camarines Norte, Philippines - Dela Cruz, Kyla Mae T.; Madayag, Juniela Anne T.; Arpa, Maria Carmencita B.; Samaniego, Jessie O.; Peregrino, Fern Rose A.; Quierrez, Rico Neil M.; Tanciongco, Alexandria M. (Journal of Degraded and Mining Lands Management, 2025)
The municipalities of Jose Panganiban and Paracale, Camarines Norte, are notable “mining districts,” where small-scale miners use mercury (Hg) to extract gold, despite its being banned under Republic Act 7076 of the People’s Small Scale Mining Act of 1991. In this study, 17 sediment samples from coastal/marine, river, and mine tailings were collected and analyzed for the following: (1) pollution assessment of potentially toxic elements (PTE), (2) total Hg concentration on particle size distribution, and (3) mercury speciation. The results showed that mercury (Hg) and arsenic (As) were the most significant pollutants and contaminants. Enrichment levels using Enrichment Factor (EF) ranked as Hg > Cr > Zn > Ni > As > Fe > Cu > V > Mn > Sr > Ca. Geoaccumulation Index (Igeo) and Potential Ecological Risk Factor (Er) confirmed that As and Hg posed the highest environmental threats, with Hg likely coming from mining and As naturally occurring but disturbed by mining activities. The mercury concentration patterns varied by location, where river sediments concentrated Hg in medium silt, coastal sediments had scattered Hg levels due to more extended transport, and mine tailings had irregular Hg distribution since they were the source. Moreover, the mercury speciation showed a consistent result of Hg (I) among all the samples and a remarkable peak for Hg0 with the tailings samples, suggesting incomplete oxidation from mining.